HUMAN GOVERNANCE FOR EXCELLENT ORGANIZATIONS - Miloš Jelić; Ana Aksentijević Jelić (Proceedings on Engineering Sciences, 2019)
Every excellent organization derive from leadership. Leaders in organizations accomplish their future through core purpose that is grounded on vission, mission, values and corporate behaviour. Organization values and role models for integrity and ethical behaviour make part of corporate governance that is primarilly aimed to raise profit and enhance organisation’s reputation. However, leaders in excellent organisations inspire people and create a culture of involvement, empowerment and accountability. They also promote a culture which incites the generation of new ideas and new way of thinking what may lead to inovation and organisational development. To be effective these leader’s actions require people to possess two characteristics that are not recognized within corporate governance: self-consciousness and self-accountability, but they are the pillars of other approach - human governance. Ostensibly, to be successful excellent organization leader has to combine these two distinct approaches what the authors of the paper try to elucidate.